Bullying Behavior on The Character of Students Through Self-Control and Social Control in Madrasah Special Region of Yogyakarta - Nur Irsyadiah; Maryam Sulaeman; Yuli Marlina (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
The true character is attached to the student. The learning process taken makes students know what is good and what is not good, but it turns out that this is not enough to minimize bullying behavior that occurs in other students, this often happens even in a conscious state. Often from the act of bullying behavior where the victim takes negative action for the treatment he receives, bullying behavior becomes one of the verbal crimes that have a high risk to the victim. Through social control, it is hoped that it will be able to reduce or even eliminate this behavior among students. By increasing social control, it is hoped that students can show an educated attitude by not engaging in bullying behavior among themselves. This study uses quantitative methods to calculate the correlation needed by research data. The purpose of this research is to understand bullying behavior on the character of students through self-control and social control. The method used is qualitative research. The research was conducted at MA DIY, Special Region of Yogyakarta. Data were obtained from the results of in-depth interviews with key informants: school principals, vice principals, teachers, and students. The data were analyzed using the steps: data reduction, data display, and conclusion/verification.